2013
DOI: 10.3844/ajavsp.2013.146.151
|View full text |Cite
|
Sign up to set email alerts
|

POLYMERASE CHAIN REACTION DETECTION OF <i>PASTEURELLA MULTOCIDA</i> TYPE B: 2 IN MICE INFECTED WITH CONTAMINATED RIVER WATER

Abstract: Hemorrhagic septicemia is an acute, deadly disease of cattle and buffaloes associated with colossal economic loss in the livestock industry in the Asian regions particularly Malaysia. Therefore, this study was conducted to investigate on the Polymerase chain reaction detection of Pasteurella multocida type B: 2 in mice inoculated through different routes with river water contaminated with infected mice carcasses. Sixty five mice were used for the study; five mice were placed in each tank containing rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Rivers and streams have been thought to be responsible for the transmission of haemorrhagic septicemia through carcasses washed down from one village upstream to another further down the rivers (Khaleel et al, 2013). In fact HS has been associated with the monsoon seasons (Abdullah et al, 2013a) and dumping of infected carcasses into streams and rivers. Khaleel et al (2014) Stated that there is dissemination and multiplication of P. multocida B: 2 in vital organs after intranasal and subcutaneous challenge in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Rivers and streams have been thought to be responsible for the transmission of haemorrhagic septicemia through carcasses washed down from one village upstream to another further down the rivers (Khaleel et al, 2013). In fact HS has been associated with the monsoon seasons (Abdullah et al, 2013a) and dumping of infected carcasses into streams and rivers. Khaleel et al (2014) Stated that there is dissemination and multiplication of P. multocida B: 2 in vital organs after intranasal and subcutaneous challenge in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In another study in the same area, the highest prevalence of HS disease was in a canal irrigated area of Rahim Yar Khan District in Punjab (Khan, ). It was also postulated recently that HS outbreaks among cattle and buffaloes could be due to using contaminated river water with HS carcasses (Abdullah et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that bacteria was shed into the water and was successfully recovered and inoculated into susceptible mice through various routes of inoculation. Earlier, Abdullah et al (2013b) had reported the successful recovery of P. multocida using PCR from various organs of mice inoculated with contaminated river water. HS is a deadly infection and the extent of lesion manifestation depends on the duration of the disease and the dose of bacterial inoculums (Kharb and Charan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The disease is caused by serotypes B and E strains of Pasteurella multocida (Kharb and Charan, 2012;Khaleel et al, 2013;Abdullah et al, 2013a;. HS is widespread in most parts of tropical Asia and Africa.…”
Section: Introductionmentioning
confidence: 99%